The impact of cultural diversity on innovation: Evidence from Dutch firm-level data - Ceren Ozgen; Peter Nijkamp; Jacques Poot (Institute for the Study of Labor (IZA), 2011)
Due to the growth in international migration in recent decades, the workforce of firms in host countries has become considerably more diverse, both demographically and culturally. It is an important question for firms and for governments to ask whether there are some productivity-enhancing externalities gained from this growing diversity within firms. In recent years migration research has demonstrated positive economic impacts of cultural diversity on productivity and innovation at the regional level. However, there is a dearth of research on the links between innovation and migrant diversity at the firm level. In this paper we construct and analyse a unique linked employer-employee micro-dataset of 4582 firms, based on survey and administrative data obtained from Statistics Netherlands. Excluding firms in the hospitality industry and other industries that employ low-skilled migrants, we use the local number of restaurants with foreign cuisines and the historical presence of migrant communities as valid instruments of endogenous migrant settlement. We find that firms in which foreigners account for a relatively large share of employment are somewhat less innovative. However, there is strong evidence that firms that employ a more diverse foreign workforce are more innovative, particularly in terms of product innovations.
urn:nbn:de:101:1-201110263380
Keywords: D22; F22; O31; 330; immigration; innovation; cultural diversity; knowledge spillovers; linked employer-employee data; Netherlands; Migranten; Diversity Management; Multikulturelle Gesellschaft; Innovation; Wissenstransfer; Produktivität; Schätzung; Niederlande